A degradable prepreg material and its preparation method and application
By using a modified epoxy resin containing acetoacetate group and bisphenol A epoxy resin, the problem of difficult degradation of existing prepreg cloth materials after curing is solved, and rapid curing, flame retardant and degradable prepreg cloth materials are achieved, which improves the value of recycling.
Patent Information
- Application Number
- CN202510008537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
The existing prepreg cloth materials are difficult to degrade after curing, resulting in difficulty in disposal of waste, serious environmental pollution, and lack of flame retardant and design flexibility.
A modified epoxy resin containing acetoacetate group was used to pair it with bisphenol A epoxy resin and react with different combinations of curing agents to prepare a prepreg cloth material with rapid curing, flame retardant and degradable characteristics.
It realizes the rapid curing and flame retardant effect of prepreg cloth materials, and has good degradability properties, and the separation rate can reach more than 60%, greatly improving the value of recycling.
Smart Images

Figure BDA0005227662440000041 
Figure BDA0005227662440000051 
Figure BDA0005227662440000061
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer compound compositions, and in particular to a degradable prepreg material and a preparation method and application thereof. Background Art
[0002] Prepreg materials are widely used in rail transit, new energy vehicles and other fields. With the advancement of technology, there are demands for fast curing, flame retardancy, flexible design and environmental protection. However, with the increase in the amount of waste, the post-processing of prepreg materials faces huge pressure. Traditional treatment methods are mostly crushing, landfilling, incineration, etc., which cause serious environmental pollution, high energy consumption, and waste of raw materials. Therefore, it is very important to develop a prepreg material that can be quickly cured, flame retardant, degradable, and recyclable.
[0003] Chinese invention patent CN117024919A discloses a degradable inner mold material suitable for carbon fiber special-shaped parts, wherein epoxy resin, modified spirocyclic amine, fumed silica, and phosphoric acid-modified branched polyester are mixed to obtain a mold material for carbon fiber special-shaped parts, and the inner mold can be degraded in an organic acid solution after the carbon fiber prepreg is cured and formed, but it does not have a flame retardant effect. Chinese invention patent CN113651934A discloses a preparation and degradation method of a boride-modified thermosetting phenolic resin and a composite material thereof, wherein the modified thermosetting phenolic resin can effectively solve the problem of large bulk viscosity and poor film-forming property when the existing thermosetting phenolic resin is synthesized by a hot melt prepreg process, but the modified phenolic resin used is thermosetting and cannot meet the demand for flexible design. Summary of the invention
[0004] In order to develop a prepreg material that can be quickly cured, flame retardant, degradable, and recyclable, the first aspect of the present invention provides a degradable prepreg material, which, in terms of weight percentage, comprises 15-50% of an epoxy resin compound and 50-85% of a fiber raw material, wherein the epoxy resin compound comprises at least a modified epoxy resin.
[0005] As a preferred embodiment, the molecular structure of the modified epoxy resin at least includes acetoacetate bonds.
[0006] The inventors found in the experimental process that the modified epoxy resin containing acetoacetate groups and bisphenol A epoxy resin can be used to react with different combinations of curing agents to obtain prepregs with different curing speeds and flame retardant effects, which has good application prospects in multiple industries. The reason may be that the modified epoxy resin containing acetoacetate groups can be cured together with dicyandiamide and organic urea, which can have a shorter curing time and improve the curing speed. At the same time, the inventors further found that the modified epoxy resin contains chain phosphorus-containing structures and cyclic phosphorus-containing structures, and the obtained resin also has a certain flame retardant effect, which can reduce the addition of flame retardants, reduce costs, improve the compatibility of the modified resin compounds, and have broader application prospects.
[0007] As a preferred embodiment, the molecular structure of the modified epoxy resin further includes a phosphorus-containing bond, and the phosphorus-containing bond includes at least one of a chain phosphorus bond or a cyclic phosphorus bond.
[0008] As a preferred embodiment, the phosphorus-containing compound bonds include P-Ph bonds, P=O bonds, and POC bonds.
[0009] As a preferred embodiment, the mass fraction of phosphorus in the modified epoxy resin is 1-4%.
[0010] In addition, the acetoacetate group in the modified epoxy resin can be degraded by heating with amine compounds in an alkaline environment. The amine group and the acetoacetate group combine to form a dynamic enamine bond to achieve a decomposition effect, thereby realizing the separation of the resin and the fiber. The modified resin compound has good degradable properties, and the separation rate can reach more than 60%, greatly improving the value of recycling.
[0011] As a preferred embodiment, the degradation temperature of the degradable prepreg material is 100-200° C., and the degradation time is 6-24 hours.
[0012] As a preferred embodiment, the raw materials for preparing the epoxy resin compound include, by weight, 50-80 parts of epoxy resin matrix, 3-15 parts of modified epoxy resin, 30-50 parts of flame retardant, 5-15 parts of curing agent, and 2-10 parts of accelerator.
[0013] As a preferred embodiment, the epoxy resin matrix includes but is not limited to bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, etc.
[0014] As a preferred embodiment, the preparation method of the modified epoxy resin comprises the following steps:
[0015] M1 heats the epoxy resin to 90-100°C;
[0016] Add DOPO to M2 and stir at constant temperature until DOPO is completely melted;
[0017] Add triphenylphosphine catalyst into M3, gradually raise the temperature to 120-160°C, and react at constant temperature for 4-6 hours to obtain the product.
[0018] As a preferred embodiment, the epoxy resin is purchased from Shangwei New Materials Technology Co., Ltd., model number is RF610.
[0019] As a preferred embodiment, the addition amount of the DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) accounts for 5-35wt% of the mass of the epoxy resin; the addition amount of the triphenylphosphine catalyst accounts for 5-15wt% of the total mass.
[0020] As a preferred embodiment, the added amount of the DOPO accounts for 30 wt% of the epoxy resin mass; the added amount of the triphenylphosphine catalyst accounts for 10 wt% of the total mass.
[0021] As a preferred embodiment, the CAS number of the triphenylphosphine catalyst is 603-35-0.
[0022] As a preferred embodiment, the curing agent is a latent curing agent, selected from at least one of dicyandiamide, 4,4'-diaminodiphenyl sulfone, and hydrazide compound curing agents; the accelerator is a latent curing accelerator, selected from at least one of organic urea and modified imidazole curing accelerators.
[0023] As a preferred embodiment, the infrared spectrum of the modified epoxy resin is between 1760-1710 cm -1 There is a characteristic peak of acetoacetate group at 1550-1600cm -1 There are P-Ph characteristic peaks at 1180-1220cm -1 There is a P=O characteristic peak at 920-990cm -1 There is a POC characteristic peak at . For specific infrared spectra, see Figure 1 .
[0024] As a preferred embodiment, the flame retardant includes but is not limited to aluminum hydroxide, antimony trioxide, zinc borate, APP (ammonium polyphosphate), MPP (melamine polyphosphate), and MCA (melamine cyanurate).
[0025] As a preferred embodiment, the preparation process of the epoxy resin compound comprises the following steps:
[0026] The epoxy resin matrix, modified epoxy resin, flame retardant, curing agent and accelerator are uniformly mixed according to a proportion to obtain an epoxy resin compound.
[0027] As a preferred embodiment, the fiber raw material is selected from at least one of glass fiber, carbon fiber, basalt fiber, boron fiber, asbestos fiber and metal fiber.
[0028] A second aspect of the present invention provides a method for preparing a degradable prepreg material, comprising the following steps:
[0029] S1 heats and melts the epoxy resin compound, and evenly applies it to the release material to obtain an adhesive film;
[0030] S2 arranges the fiber raw materials neatly according to the design;
[0031] S3 adheres the adhesive film to both sides of the neatly arranged fiber raw materials, and heats and presses to melt the epoxy resin compound and infiltrate the fiber raw materials;
[0032] S4 impregnates the fiber raw material, cools it down and sets it, peels off the release material, and obtains the degradable prepreg material.
[0033] As a preferred embodiment, the heating temperature in step S1 is 60-90° C., the heating temperature in step S3 is 70-100° C., and the pressurization pressure is 1-5 MPa.
[0034] The third aspect of the present invention provides an application of a degradable prepreg material, which is applied to molding, rolling rod, pressure bag, and autoclave molding processes, with a molding and curing temperature of 120-180° C. and a curing time of 5-30 min.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The degradable prepreg material of the present invention uses a modified epoxy resin containing acetoacetate groups and a bisphenol A epoxy resin and reacts with different combinations of curing agents to obtain prepregs with different curing speeds, which has good application prospects in multiple industries.
[0037] (2) The biodegradable prepreg material of the present invention adopts a modified epoxy resin containing a phosphorus compound, and the obtained resin also has a certain flame retardant effect, which can reduce the addition of flame retardants, reduce costs, improve the compatibility of the modified resin compound, and have a broader application prospect.
[0038] (3) The degradable prepreg material of the present invention has good degradability and a separation rate of more than 60%, which greatly improves the value of recycling.
[0039] (4) The degradable prepreg material of the present invention can be designed to simultaneously meet different requirements of rapid curing and flame retardancy, thereby greatly reducing production costs and improving production efficiency. It has good application prospects in the fields of rail transit, new energy vehicles, etc.
[0040] (5) The degradable prepreg material of the present invention has good degradability after being applied to composite material products, and the resin and fiber can be recycled for reuse, which has good economic benefits and avoids the waste of resources and environmental pollution caused by the disposal of composite material waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the infrared spectrum of modified epoxy resin. DETAILED DESCRIPTION
[0042] Embodiment 1
[0043] Examples 1-3, Comparative Example 1 provides raw materials and a process for preparing an epoxy resin compound. The raw materials are shown in Table 1 in parts by weight.
[0044] Table 1
[0045]
[0046]
[0047] The bisphenol A epoxy resin was purchased from the Epoxy Resin Factory of Nanya Electronic Materials (Kunshan) Co., Ltd., with the brand name NPEL-128;
[0048] The preparation method of the modified epoxy resin comprises the following steps:
[0049] M1 heats the epoxy resin to 100°C;
[0050] Add DOPO to M2 and stir at constant temperature until DOPO is completely melted;
[0051] Add triphenylphosphine catalyst into M3, gradually raise the temperature to 140°C, and react at constant temperature for 5 hours to obtain the product.
[0052] The epoxy resin was purchased from Shangwei New Materials Technology Co., Ltd., model number RF610.
[0053] The added amount of the DOPO is 30 wt %; the added amount of the triphenylphosphine catalyst accounts for 10 wt % of the total mass.
[0054] The infrared spectrum of the modified epoxy resin obtained is shown in Figure 1 .
[0055] The preparation process of the epoxy resin compound comprises the following steps:
[0056] The epoxy resin matrix, modified epoxy resin, flame retardant, curing agent and accelerator are uniformly mixed according to a proportion to obtain an epoxy resin compound.
[0057] Performance Testing
[0058] 1. Gelation time: Place the prepared epoxy resin compound on a 150°C heated iron plate to test the gelation time;
[0059] 2. Flame retardancy: Use methane flame to ignite for 15 seconds and then evacuate the flame. Observe the continuous burning time of the flame to evaluate the flame retardancy.
[0060] 3. Degradability: The samples of Examples 1-3 and Comparative Example 1 were cut into the same size, heated at 150°C for 8 hours in a liquid amine compound with the same pH value>10, and the degradation was observed. O means degradation; × means no degradation.
[0061] The test results are shown in Table 2 below.
[0062]
[0063] Conclusion: The curing speed of the resin can be adjusted by adjusting the type and ratio of the curing agent and the accelerator. The addition of flame retardant can effectively improve the flame retardant effect of the resin. The modified degradable epoxy resin contains cyclic or chain phosphorus-containing structures, which can enhance the flame retardant effect of the resin and also have a degradation effect, so that the resin can be heated and degraded under alkaline conditions.
[0064] Embodiment 2
[0065] Examples 2-8, Comparative Example 2 provides a degradable prepreg material and a preparation method. The preparation raw materials are shown in Table 3.
[0066] Table 3
[0067]
[0068]
[0069] The bisphenol A epoxy resin was purchased from the Epoxy Resin Factory of Nanya Electronic Materials (Kunshan) Co., Ltd., with the brand name NPEL-128
[0070] The brominated epoxy resin was purchased from the Epoxy Resin Factory of Nanya Electronic Materials (Kunshan) Co., Ltd., with the brand name NPEB-400.
[0071] The preparation method of the modified epoxy resin is the same as that of Example 1. The fiber raw material of Examples 1-6, 8 and Comparative Example 1 is 200 g / m 2The glass fiber woven cloth was purchased from Foshan Changyu New Material Technology Co., Ltd., with a brand name of EW200; the fiber raw material of Example 7 was FAW of 100 g / m 2 The unidirectional carbon fiber was purchased from TORAY Co., Ltd. with the brand number T700SC-12K.
[0072] A method for preparing a degradable prepreg material comprises the following steps:
[0073] S1 heats and melts the epoxy resin compound, and evenly applies it to the release material to obtain an adhesive film;
[0074] S2 arranges the fiber raw materials neatly according to the design;
[0075] S3 adheres the adhesive film to both sides of the neatly arranged fiber raw materials, and heats and presses to melt the epoxy resin compound and infiltrate the fiber raw materials;
[0076] S4 impregnates the fiber raw material, cools it down and sets it, peels off the release material, and obtains the degradable prepreg material.
[0077] The heating temperature in step S1 is 90° C., the heating temperature in step S3 is 100° C., and the pressurizing pressure is 3 MPa.
[0078] Embodiments 4, 5, 7, and 8 provide an application of a degradable prepreg material, comprising the following steps:
[0079] The biodegradable prepreg material was cut into 500×500 mm square pieces, two layers were laid in the same direction, and cured at 150° C. for 5 min to obtain an FRP sheet.
[0080] Embodiment 6 provides an application of a degradable prepreg material, comprising the following steps:
[0081] The biodegradable prepreg material was cut into 500×500 mm square pieces, two layers were laid in the same direction, and cured at 140° C. for 5 min to obtain an FRP sheet.
[0082] Comparative Example 2 provides an application of a degradable prepreg material, comprising the following steps:
[0083] The biodegradable prepreg material was cut into 500×500 mm square pieces, two layers were laid in the same direction, and cured at 150° C. for 30 min to obtain an FRP sheet.
[0084] Performance Testing
[0085] 1. Gelation time: Place the prepared epoxy resin compound on a 150°C heated iron plate to test the gelation time;
[0086] 2. Flame retardancy: Use methane flame to ignite for 15 seconds and then evacuate the flame. Observe the continuous burning time of the flame to evaluate the flame retardancy of the FRP sheet.
[0087] 3. Degradability: The FRP plates of Examples 4-8 and Comparative Example 2 were cut into the same size, heated at 150°C for 8 hours in a liquid amine compound with the same pH value>10, and the degradation was observed. O means degradation; × means no degradation.
[0088] 4. Glass transition temperature Tg: Under the curing conditions of 150°C × 60min, the glass transition temperature is tested with reference to ISO 11357-2 standard.
[0089] The test results are shown in Table 4.
[0090] Table 4
[0091]
[0092] 5. Degradation performance evaluation:
[0093] (1) The FRP plates of Examples 4-8 and Comparative Example 2 were cut into the same size and subjected to degradation (the FRP plates were placed in a liquid amine compound with a pH value of more than 10, heated to 150°C, kept at a constant temperature and stirred for 4 hours). After the degradation was completed, the recovered liquid and solid recovered material (including residual resin and fiber) were obtained, the weight of the solid recovered material was weighed, and the solid recovery ratio was calculated. The calculation formula is: solid recovery ratio = (original plate weight - solid recovered material weight) / original plate weight × 100%.
[0094] (2) Compare the theoretical solid recovery ratio with the actual solid recovery ratio to obtain the separation rate: Separation rate (%) = 1 - ((actual solid recovery ratio - theoretical solid recovery ratio) / theoretical resin ratio)) × 100%.
[0095] Theoretical resin ratio = 1-fiber material ratio = 40%
[0096] The test results are shown in Table 5.
[0097] Table 5
[0098] Theoretical solid recovery ratio (%) Actual solid recovery ratio (%) Separation rate (%) Example 4 60 75 62.5 Example 5 60 73 69.1 Example 6 60 77 57.5 Example 7 60 73 69.1 Example 8 60 64 90 Comparative Example 2 60 100 0
[0099] Conclusion: By adding modified epoxy resin, the cured prepreg material can be degraded, and the degradation rate can be greater than 60%, which means that most of the resin can be recycled.
[0100] From the above test results, it can be seen that the degradable fast-curing flame-retardant prepreg material disclosed in the present invention has a faster curing speed than conventional prepreg resin, which greatly reduces production costs, improves production efficiency, and has no significant attenuation in heat resistance. Through the formulation of the formula, different curing speeds and flame retardancy requirements can be met. At the same time, the cured FRP sheet is degradable, and the resin and fiber can be separated to achieve material reuse.
Claims
1. A degradable prepreg material, characterized in that: In terms of weight percentage, the preparation raw materials include 15-50% of epoxy resin compound and 50-85% of fiber raw materials, and the epoxy resin compound includes at least modified epoxy resin.
2. The degradable prepreg material according to claim 1, characterized in that: The molecular structure of the modified epoxy resin at least includes an acetoacetate bond.
3. The degradable prepreg material according to claim 1, characterized in that: The molecular structure of the modified epoxy resin also includes phosphorus-containing bonds, and the phosphorus-containing bonds include at least one of chain phosphorus bonds or cyclic phosphorus bonds.
4. The degradable prepreg material according to claim 3, characterized in that: The mass fraction of phosphorus in the modified epoxy resin is 1-4%.
5. The degradable prepreg material according to claim 1, characterized in that: In parts by weight, the raw materials for preparing the epoxy resin compound include 50-80 parts of epoxy resin matrix, 3-15 parts of modified epoxy resin, 30-50 parts of flame retardant, 5-15 parts of curing agent, and 2-10 parts of accelerator.
6. The degradable prepreg material according to claim 5, characterized in that: The curing agent is a latent curing agent, selected from at least one of dicyandiamide, 4,4'-diaminodiphenyl sulfone, and hydrazide compound curing agents; the accelerator is a latent curing accelerator, selected from at least one of organic urea and modified imidazole curing accelerators.
7. The degradable prepreg material according to claim 1, characterized in that: The fiber raw material is selected from at least one of glass fiber, carbon fiber, basalt fiber, boron fiber, asbestos fiber and metal fiber.
8. A method for preparing the degradable prepreg material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1 heats and melts the epoxy resin compound, and evenly applies it to the release material to obtain an adhesive film; S2 arranges the fiber raw materials neatly according to the design; S3 adheres the adhesive film to both sides of the neatly arranged fiber raw materials, and applies heat and pressure to melt the epoxy resin compound and infiltrate the fiber raw materials; S4 impregnates the fiber raw material, cools it down and sets it, peels off the release material, and obtains the degradable prepreg material.
9. The method for preparing the degradable prepreg material according to claim 8, characterized in that: The heating temperature in step S1 is 60-90° C., the heating temperature in step S3 is 70-100° C., and the pressurization pressure is 1-5 MPa.
10. An application of the degradable prepreg material according to any one of claims 1 to 7, characterized in that: Applicable to molding, rolling rod, pressure bag, autoclave molding process, molding curing temperature is 120-180℃, curing time is 5-30min.
Citation Information
Patent Citations
Preparation and degradation methods of boride modified thermosetting phenolic resin and composite material thereof
CN113651934A
Degradable internal mold material suitable for carbon fiber special-shaped part
CN117024919A